2018
DOI: 10.1515/adms-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubular Oxide Layers and Hydroxyapatite Coatings on Porous Titanium Alloy Ti13Nb13Zr

Abstract: The surface condition of an implant has a significant impact on response occurring at the implant-biosystem border. The knowledge of physical-chemical and biological processes allows for targeted modification of biomaterials to induce a specified response of a tissue. The present research was aimed at development of technology composing of obtaining the nanotube oxide layers on a porous titanium alloy Ti13Nb13Zr, followed by the deposition of phosphate coating. The porous substrate (porosity about 50%) was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The Pourbaix diagram shows that titanium is a metal that passivates very quickly [86]. The natural, very good corrosion resistance of titanium and its alloys is indicated [87][88][89][90][91]. Additionally, the corrosion behavior is influenced by the presence of β-stabilizing alloying elements and their role in the stability and thickness of the passive layer formed [92].…”
Section: Corrosionmentioning
confidence: 99%
“…The Pourbaix diagram shows that titanium is a metal that passivates very quickly [86]. The natural, very good corrosion resistance of titanium and its alloys is indicated [87][88][89][90][91]. Additionally, the corrosion behavior is influenced by the presence of β-stabilizing alloying elements and their role in the stability and thickness of the passive layer formed [92].…”
Section: Corrosionmentioning
confidence: 99%
“…It is expected that organized nanotubular complex oxides will form during the α phase, whereas a combination of nanotubes and nanopores will grow during the two-phase (α + β) component [41]. Several studies have reported on the surface modification of ternary Ti-30Nb-xZr [42]; Ti-35Nb-5Zr, Ti-35Nb-10Zr, and Ti-35Nb-15Zr [43]; Ti-35Nb-2Zr and Ti-35Nb-4Zr [44]; and Ti-13Nb-13Zr [45,46]. This has brought valuable knowledge on important process parameter choices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the metal substrate, nanostructures can also be formed using anodization on Ti alloy substrates, such as Ti-6Al-7Nb, 8,21 Ni-Ti, 22,23 Ti-6Al-4V, 7 Ti13Nb13Zr 24, 25 and Ti15Mo. 26 Among the many nanostructured oxide materials, TiO 2 -based nanostructures have signicant characteristics, such as improved ion-exchangeable ability, photocatalytic properties, environmental safety, and nontoxicity. However, the formation of TiO 2 microspikes on titanium substrate by electrochemical anodization process and their biomedical applications, such as drug delivery or intracellular delivery, have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%